KAJIAN YURIDIS PUTUSAN PRAPERADILAN ATAS PENANGKAPAN RAVIO PATRA (Studi Kasus Putusan Pengadilan Nomor 63/Pid.Prap/2020/PN.Jkt.Sel) - Yoga Apriansah (Universitas Semarang, 2021)
South Jakarta District Court pretrial decision Number 63 / Pid.Prap / 2020 / PN.Jkt.Sel on July 14, 2020 on behalf of pretrial applicant Ravio Patra Asri against the Head of the Regional Police (Kapolda) Metro Jaya is the main study in this research. This research is a normative juridical study using a normative legal approach and a case approach that focuses on judges' considerations to arrive at their decisions. The purpose of this research is basically to find out the judges' considerations in rejecting pretrial applications with invalid applications for arrest, searches and confiscation in pretrial institutions. The pretrial institution as a form of horizontal oversight between the relevant law enforcers, such as police, prosecutors and judges, must work effectively. This form of supervision is carried out so that no law enforcer is negligent or arbitrary in carrying out their duties. All forms of arrest, search and confiscation have been clearly regulated and must not be overridden by the applicable standard operating conditions. Examples include assignment warrants, confiscation warrants, search warrants, arrest warrants, and so on. If the action is not based on a letter or statutory provisions in force, then the action not based on law and becomes invalid